Sistem Informasi Manajemen Transaksi Layanan Fotografi di Qlise Photography - Al Faruqi, Muhammad Haidar; Sudarmilah, Endah (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2024)
The rapid digital development has driven Qlise Photography, a provider of photography services including wedding, prewedding, and studio photography, to address the complexity in managing its services. The aim of this research is to enhance the efficiency in managing and booking photography services provided by Qlise Photography through the development of a Website-Based Information System. To tackle the challenges in managing services like wedding, prewedding, and studio photography, the primary approach adopted in this research is the waterfall method, utilizing PHP programming language and leveraging CodeIgniter Framework as the development tool. The findings of this research have positively impacted Qlise Photography, with the implementation of an optimal system. Previously manual, the process of booking photography services can now be accessed and managed efficiently through the online platform. System testing using the Black Box method and the application of the System Usability Scale (SUS) yielded a score of 77, categorizing it as GOOD, indicating a positive acceptance rate from users. This marks a significant step in improving customer experience and operational efficiency in addressing the challenges of photography services in the digital era.